Short CRP for Anterior Canalithiasis: A New Maneuver Based on Simulation With a Biomechanical Model - D'Albora Rivas, Ricardo; Teixido, Michael; Casserly, Ryan M.; Mónaco, María Julia (Frontiers in Neurology, 2020)
Introduction/Objective: Anterior canalithiasis is an uncommon and challenging diagnosis. This is due in part to the difficulty of defining the affected side, the extreme positioning required to carry out described therapeutic maneuvers, and the infrequent use of specific maneuvers. Our objective is to present a new treatment alternative for anterior canalithiasis which is based on the well-known canalith repositioning procedure (CRP) described by Epley and which is used routinely in the treatment of both posterior and anterior canalithiasis. Analysis of the standard CRP for anterior canalithiasis with a biomechanical model validates that this new maneuver is an enhanced treatment option for anterior canalithiasis. We call the new maneuver the “short CRP.” Methods: A previously published 3D biomechanical model of the human labyrinths for the study of BPPV was used to analyze the conventional CRP in the treatment of anterior canalithiasis. The expected position of free otoliths near the anterior ampulla of the anterior semicircular duct was followed while recreating the sequential positions of the CRP. Although the standard CRP was possibly effective, certain enhancements were evident that could increase successful repositioning. These enhancements were incorporated into the modification of the CRP presented here as the “short CRP” for anterior canalithiasis. Results: The traditional CRP used for posterior canalithiasis can also be used for anterior canalithiasis. Although in the traditional CRP the head hangs 30° below horizontal, our simulation shows that a 40° head-hang below horizontal is an enhancement and may ensure progression of anterior otolith debris. Elimination of Position 4 of the classic CRP, in which the face is turned 45° toward the floor, was also seen as an enhancement as this position is predicted to cause retrograde movement of otoliths back into the anterior canal if the patient tucks the chin in position 4 or when sitting up. Conclusion: A modification of the CRP called the “short CRP” can be used to treat anterior canalithiasis. Model analysis predicts possible increased efficacy over the standard CRP. Model analysis of existing BPPV treatments is a valuable exercise for examination and can lead to realistic enhancements in patient care.